From Mysticism to Modernity: The Evolution of Kebatinan Traditions In Indonesia - Wijaya Wijaya (Yayasan Adra Karima Hubbi, 2024)
Background. Spirituality in Indonesia has deep roots in mystical traditions that have been passed down from generation to generation. Previously, spirituality was only practiced by certain groups who had certain spiritual understandings and experiences. However, in recent decades, spirituality in Indonesia has undergone a significant transformation. This change involves not only how spirituality is practiced, but also how spirituality is accepted and adapted by the wider community, including the younger generation. This research aims to understand the process of spiritual evolution, from practices limited to exclusive groups to more inclusive and relevant to modern life that is increasingly open to technology and globalization. Purpose. This research aims to explore how spirituality in Indonesia adapts to social and technological developments, as well as how the younger generation integrates spirituality into their lives. Method. This study uses a qualitative approach with a case study design, which involves in-depth interviews and observations of the spiritual community in Java. Data was collected from a variety of respondents with different educational backgrounds and ages. Results. The results of the study show that spirituality has transformed to be more inclusive, with the influence of technology and social media that allows the spread of its teachings to a wider audience, including the younger generation. In addition, spirituality also underwent changes in the form of currents, such as the adoption of Contemporary Sufi teachings. Conclusion. Spirituality in Indonesia has adapted to the changing times, maintained its traditional values, and integrated technology in its practice. This research shows that spirituality has the potential to continue to develop in the midst of modernity and globalization.